2008
DOI: 10.1364/oe.16.016124
|View full text |Cite
|
Sign up to set email alerts
|

Impact of XPM and FWM on the digital implementation of impairment compensation for WDM transmission using backward propagation

Abstract: The impact of cross-phase modulation (XPM) and four-wave mixing (FWM) on electronic impairment compensation via backward propagation is analyzed. XPM and XPM+FWM compensation are compared by solving, respectively, the backward coupled Nonlinear Schrödinger Equation (NLSE) system and the total-field NLSE. The DSP implementations as well as the computational requirements are evaluated for each post-compensation system. A 12 x 100 Gb/s 16-QAM transmission system has been used to evaluate the efficiency of both ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(62 citation statements)
references
References 19 publications
1
61
0
Order By: Relevance
“…The impact of varying the step size in DBP has been investigated previously in [4][5][6][7] only for single channel DBP. In [18][19][20] this has been investigated for a simplified implementation of DBP, where interchannel nonlinearity was compensated coupling the reverse NLSE for each channel. However, in a transmission scenario where the channels are nearly symbol rate spaced, this may lead to a significant penalty compared to a full-field DBP where the phase relationship between channels is preserved and the entire spectrum is jointly backpropagated.…”
Section: Impact Of Dsp Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of varying the step size in DBP has been investigated previously in [4][5][6][7] only for single channel DBP. In [18][19][20] this has been investigated for a simplified implementation of DBP, where interchannel nonlinearity was compensated coupling the reverse NLSE for each channel. However, in a transmission scenario where the channels are nearly symbol rate spaced, this may lead to a significant penalty compared to a full-field DBP where the phase relationship between channels is preserved and the entire spectrum is jointly backpropagated.…”
Section: Impact Of Dsp Parametersmentioning
confidence: 99%
“…In [18][19][20] the effect of the number of steps per span has been studied for a low-complexity version of multichannel DBP taking into account only incoherent nonlinear effects (SPM and XPM) for coarsely spaced WDM channels. In this paper we present the first quantitative study of the efficacy of multichannel DBP jointly considering parameters such as step size, sampling rate, PMD and the bandwidth of the backpropagated signal, for spectrally efficient Nyquist-spaced WDM channels.…”
Section: Introductionmentioning
confidence: 99%
“…Various techniques have been proposed to mitigate nonlinear impairments with the use of optical signal processing [3,4] and more recently also digital signal processing (DSP) [5][6][7]. It was recently shown that co-propagating phaseconjugated twin waves (PCTWs) experience anti-correlated nonlinear distortions, and nonlinearity mitigation can be achieved by coherently superimposing the twin waves at the receiver [8], effectively trading spectral efficiency for ultra-long-haul performance.…”
Section: Introductionmentioning
confidence: 99%
“…Among these techniques, the digital backward propagation (DBP) method has proved to be quite promising for jointly compensating linear and nonlinear impairments [9]. This method is based on solving the nonlinear Schrödinger equation (NLSE) in the backward direction starting with the received signal as the input and producing the signal at the transmitter as its output [10]. But as the high complexity of the NLSE when fiber loss, dispersion and nonlinearity play a crucial role in WDM systems simultaneously, one of the technically challenging for DBP is solving the NLSE effectively in a trade-off between accuracy and computational load [11].…”
Section: Introductionmentioning
confidence: 99%